PERIPETEIA IN NARRATIVE THEORY FROM ARISTOTLE TO COGNITIVE NARRATOLOGY - Saidov Sukhrob Samiyevich (Bright Mind Publishing, 2026)
Peripeteia, conventionally defined as a sudden reversal within narrative action, has occupied a central position in literary theory since its formulation in classical poetics. In Aristotle’s Poetics, the concept is primarily associated with plot structure and the causal logic of tragic action. Subsequent developments in narrative theory, however, have gradually expanded the scope of peripeteia beyond formal reversals of fortune to include shifts in cognition, emotion, and interpretation. Against this background, the present article traces the theoretical trajectory of peripeteia from Aristotelian poetics to contemporary cognitive narratology. It argues that, within cognitive approaches to narrative, peripeteia may be more productively understood as a moment of cognitive and emotional reorganization, affecting both character consciousness and reader interpretation. By bringing classical narrative theory into dialogue with cognitive models of narrative comprehension, the article proposes a reconceptualization of peripeteia as a key mechanism of narrative meaning-making and reader engagement.
Keywords: Peripeteia, narrative theory, Aristotle, cognitive narratology, mental models, emotional processing.